Surveil and perform. The supply chain of illegal timber in Peru - Mujica, Jaris; Zevallos-Trigoso, Nicolás Antonio; Campos-Vásquez, Christian (FLACSO - Sede Ecuador, 2024)
Between 37 and 63% of the logged timber in Peru has an illegal origin. This study aims to describe this supply chain in Ucayali region. The main contribution is the elaboration (and diagramming) of a sequence of processes, activities, and tasks (supported by the collection of management documents, field interviews and observation, based on the crime-script methodology), and the identification of mechanisms of evasion of environmental, tax and labour controls which explain the illegal origin. The severe gap between the supply chain and the regulatory structure developed by the State shows formal instruments supported by declarative mechanisms that lead to proposing the idea of a State that performs control, carrying out a formal theatricalization of surveillance, while assuming the existence of a widespread illegal logic.